2021
DOI: 10.4317/medoral.24009
|View full text |Cite
|
Sign up to set email alerts
|

Trend of hospitalized cases of oral cancer in Brazil and its relationship with oral health coverage in public health system between 2009 and 2017

Abstract: Background This study aimed to analyze the trend in the number of hospitalized cases of oral cancer in Brazil, according to the coverage of oral health services in public health system, and also investigate the influence of healthcare and clinical characteristics on the severity of oral cancer cases. Material and Methods This retrospective study considered the period between 2009 and 2017. Data from the Hospital Registry of Cancer from the National Cancer Institute were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(29 citation statements)
references
References 8 publications
4
25
0
Order By: Relevance
“…Nevertheless, results of the present study also demonstrated that cities with higher oral health coverage in primary care had lower number of hospitalization and lower number of deaths due to oral cancer. This corroborates a previous study from our research group, which highlighted the contribution of Brazilian National Oral Health Policy in reducing the frequency of hospitalization due to oral cancer [ 16 ]. In addition, investing in public oral health services may be an alternative to reduce social inequalities in health, and then also provide dignity and access to oral cancer prevention and treatment.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…Nevertheless, results of the present study also demonstrated that cities with higher oral health coverage in primary care had lower number of hospitalization and lower number of deaths due to oral cancer. This corroborates a previous study from our research group, which highlighted the contribution of Brazilian National Oral Health Policy in reducing the frequency of hospitalization due to oral cancer [ 16 ]. In addition, investing in public oral health services may be an alternative to reduce social inequalities in health, and then also provide dignity and access to oral cancer prevention and treatment.…”
Section: Discussionsupporting
confidence: 93%
“…In addition, the population of those cities has higher life expectancy, which increases the proportion of the risk group for advanced age, in addition to greater access to diagnosis and hospitalization [ 19 , 20 ]. Also, it was expected that larger cities, with larger population, presented major number of cases [ 16 ]. Inverse associations between MHDI and oral cancer were found in studies that evaluated mortality rates [ 9 , 10 , 20 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations